2010
DOI: 10.1080/13854040903482822
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between suboptimal cognitive effort and the clinical scales of the Personality Assessment Inventory

Abstract: Little research has examined the relationship between the Personality Assessment Inventory (PAI) and cognitive effort. The current study extends the research on personality assessment and suboptimal cognitive effort by evaluating the relationship between the PAI clinical scales and the Test of Memory Malingering (TOMM) in a neuropsychological population. Utilizing corrections for multiple comparisons, rank-order correlations with the TOMM Trial 2 (T2) and the PAI clinical scales indicated a significant relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Conversely, PVTs were significantly associated with most measures of cognitive performance, whereas associations between SVTs and cognitive tests were variable. In general, results are consistent with the extant literature indicating associations among SVTs, PVTs, symptom measures, and cognitive tests (Armistead-Jehle & Buican, 2012;Copeland et al, 2016;Lange et al, 2010Lange et al, , 2012Whiteside et al, 2010). However, the present study extended these results to demonstrate that PVTs and SVTs each explain unique variance in symptom report, whereas only PVTs explain unique variance in cognitive performance.…”
Section: Simssupporting
confidence: 91%
“…Conversely, PVTs were significantly associated with most measures of cognitive performance, whereas associations between SVTs and cognitive tests were variable. In general, results are consistent with the extant literature indicating associations among SVTs, PVTs, symptom measures, and cognitive tests (Armistead-Jehle & Buican, 2012;Copeland et al, 2016;Lange et al, 2010Lange et al, , 2012Whiteside et al, 2010). However, the present study extended these results to demonstrate that PVTs and SVTs each explain unique variance in symptom report, whereas only PVTs explain unique variance in cognitive performance.…”
Section: Simssupporting
confidence: 91%
“…Finally, there are other factors likely influencing effort, or modifying neurocognitive performance as a function of effort. Examples include personality 41,42 and acculturation 43,44 . Thus, further investigation of factors that mitigate or augment effort in the context of research studies might consider factors not considered here.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that multiple studies have shown little relationship between cognitive SVTs and feigning of psychological symptoms on personality inventories (Boone et al 1995;Nelson et al 2007;Sumanti et al 2006). However, subsequent research has demonstrated that select MMPI-2-RF validity scales (Response Bias Scale: Gervais et al 2010;FBS-r: Youngjohn et al 2011) and Somatic/Cognitive scales (Youngjohn et al 2011) and the Personality Assessment Inventory Somatic Complaints scale (Whiteside et al 2010) are effective in identifying noncredible cognitive symptom report. Thus, criterion C5 should be modified to indicate that select psychological test validity and clinical scales can be used to support cognitive symptom over-report.…”
Section: Criticism Of Criterion C: Evidence From Self-reportmentioning
confidence: 98%